PENGARUH PERSEPSI KEGUNAAN,PERSEPSI KEMUDAHAN DAN PERSEPSI RESIKO TERHADAP MINAT MENGGUNAKAN INTERNET BANKING DIKOTA BATAM - Jefry, Jefry; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2025)
The development of digital banking technology, particularly internet banking, has rapidly advanced in the digitalization era. However, the adoption of this service still faces various challenges, especially those related to user perception. This study aims to analyze the influence of perceived usefulness, perceived ease of use, and perceived risk on the interest of Batam City residents in using internet banking services. This research employs a quantitative method by collecting data through questionnaires distributed to potential internet banking users in Batam City. The obtained data is analyzed using multiple linear regression methods. The results indicate that perceived usefulness and perceived ease of use have a positive and significant effect on the intention to use internet banking, while perceived risk has a negative and significant effect. These findings suggest that increasing awareness of the benefits and ease of use of internet banking can encourage its adoption, while concerns about risks should be minimized by banks to enhance user trust. Keywords: Perceived Usefulness, Perceived Ease of Use, Perceived Risk, Intention to Use Internet Banking.